PREDICTION OF CLINICAL CONSEQUENCES OF PARKINSON'S DISEASE - Khubetova, I.V.; Gozhenko, A.I. (World of Medicine and Biology, 2022)
Parkinson's disease remains the most common neurodegenerative disease affecting 1–2 ‰ of the population. The aim of the study was to identify prognostically significant factors that determine the course of Parkinson’s disease in the short term. The study was performed on the basis of the regional clinical hospital (Odesa) in 2017–2021. The data of the examination of 364 patients with verified Parkinson’s disease , including 198 men (54.4 %) and 166 women (45.6 %), were analyzed. The average age of the patients was 63.2±0.6 years. There was found that the most significant predictors for predicting the course of Parkinson’s disease are the severity of motor and cognitive disorders, the age of onset and the duration of the disease.
Keywords: Parkinson's disease; diagnosis; prognosis; clinical outcomes; clinical monitoring